(untitled) (Modern education and development, 2025)
This article examines the level of stress, its psychological factors, and consequences among students in higher education. Literature analysis shows that academic pressure, lack of time, insufficient social support, and personal life challenges significantly affect students’ mental health. The study analyzes the effectiveness of various stress-reduction approaches, including psychological counseling, mindfulness, and anti-stress training programs. Based on the results, the necessity of developing stress management strategies within higher education institutions is substantiated.